Using Health Digital Technology for Suicide Prevention: A Systematic Review - Larasati, Dutya Intan; Anggraini, Yuli; Wahyudi, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Suicide is a serious public health problem and is currently a global concern. The World Health Organization (WHO) estimates that each year around one million people die from suicide which represents a global death rate of 16 people per 100,000 or one death every 40 seconds. Health digital technology services need to be developed, especially in countries that do not yet have an adequate mental health service system and adequate access. This study analyzed health digital technology for suicide prevention with a systematic review sight. A literature search was performed on databases from Scopus, Science Direct, PubMed, ProQuest, and Sage for the years 2015-2019. The keywords in the search are "suicide", "self injury", "prevention", "avoidance", "health technology", "digital technology", and "mHealth". Challenges in the industrial era 4.0 increase the interest of the global community to find technology-based solutions that focus on the idea of suicide and mental health. Digital technology that can be used is a self-help guide digital intervention, mobile health applications, online interactive applications that have been proven to reduce suicidal thoughts. This intervention can overcome barriers related to access to health services with the availability of health digital technology that can be accessed anywhere and anytime, thereby offering sustainable and scalable solutions. The use of health technology can be beneficial for suicide prevention programs as they are effective, efficient, inexpensive, and can reach many people.